Thrombolysis for massive pulmonary embolism in pregnancy: a case report - Fasullo, Sergio (Springer, 2011)
Mortality from pulmonary embolism (PE) in pregnancy might be related to challenges in targeting the right population for prevention. Such targeting could help ensure that the correct diagnosis is suspected and adequately investigated, and allow the initiation of the timely and best possible treatment of this disease. In the literature to date only 18 case reports of thrombolysis in pregnant women with PE have been reported, and showed beneficial effects for both mother and fetus in terms of mortality and complications with acceptable bleeding risks. We present here the case of a pregnant patient with massive PE who underwent successful thrombolysis. A 26-year-old pregnant (at 24 weeks) woman was admitted 4 h after onset of sudden acute dyspnea and chest pain. An immediate electrocardiogram showed a typical S1-Q3-T3 pattern. The echocardiogram showed a distended right ventricle with free-wall hypokinesia and displacement of the interventricular septum toward the left ventricle. Thrombolysis with recombinant tissue plasminogen activator (alteplase 10 mg bolus, then 90 mg over 2 h) was administered. Pelvic examination and ultrasound showed regular fetal heart beat, and regular placental and liquid presence. No problems developed for the mother or fetus in the subsequent days or at discharge. In conclusion, in pregnant patients with life-threatening massive PE, thrombolytic therapy can be administered, and the use of echocardiographic, laboratory, and clinical data can be useful tools to achieve a rapid diagnosis and make a therapeutic decision, but additional studies need to be performed to further define its use.